Protective Effect of Carvacrol against Gut Dysbiosis and Clostridium difficile Associated Disease in a Mouse Model - Mooyottu, Shankumar; Flock, Genevieve; Upadhyay, Abhinav; Upadhyaya, Indu; Maas, Kendra; Venkitanarayanan, Kumar (Frontiers in Microbiology, 2017)
Clostridium difficile is an anaerobic sporeforming pathogen causing a toxin-mediated enteric disease in humans. C. difficile predominantly affects hospital inpatients undergoing prolonged antibiotic therapy, which results in enteric dysbiosis, leading to C. difficile spore germination, pathogen colonization in the intestine and subsequent toxin production. Therapeutic agents that inhibit C. difficile without causing enteric dysbiosis could improve the clinical outcome of C. difficile infections. Our previous studies indicated that carvacrol (CR), a plant-derived compound significantly inhibited C. difficile toxin production and spore outgrowth in vitro. This study investigated the effect of CR on antibiotic-associated gut dysbiosis and C. difficile infection in a mouse model. Five to six-week-old C57BL/6 mice were randomly divided into seven treatment groups (challenge and control) of eight mice each. Mice were fed with irradiated feed supplemented with CR (0%, 0.05%, and 0.1%); the challenge groups were made susceptible to C. difficile by orally administering an antibiotic cocktail in water and an intra-peritoneal injection of clindamycin. Both challenge and control groups were infected with 105 CFU/ml of hypervirulent C. difficile (ATCC 1870) spores or PBS, and observed for clinical signs for ten days. Respective control groups for CR, antibiotics, and their combination were included for investigating their effect on mouse enteric microflora. Mouse body weight and clinical and diarrhea scores were recorded daily post infection. Fecal samples were collected for microbiome analysis using rRNA sequencing in MiSeq platform. Carvacrol supplementation significantly reduced the incidence of diarrhea and improved the clinical and diarrhea scores in mice (p<0.05). Microbiome analysis revealed a significant increase in Proteobacteria and reduction in the abundance of protective bacterial flora in antibiotic-treated and C. difficile-infected mice compared to controls (p<0.05). However, CR supplementation positively altered the microbiome composition, as revealed by an increased abundance of beneficial bacteria, including Firmicutes, and significantly reduced the proportion of detrimental flora such as Proteobacteria, without significantly affecting the gut microbiome diversity compared to control. Results suggest that CR could potentially be used to control gut dysbiosis and reduce C. difficile infection.